Problems of governance in South Asia - Pai Panandiker, V. A., 1935-; Centre for Policy Research (New Delhi, India) (Delhi : Konark Publishers, 2000)
Contributed articles.
"Under the auspices of Centre for Policy Research, New Delhi."
Keywords: Democracy -- South Asia; South Asia -- Politics and government